STUDI DESKRIPTIF PERILAKU PROKRASTINASI AKADEMIK PADA PESERTA DIDIK KELAS VIII SMP NEGERI 13 PONTIANAK - Widiseno, Febria Putri; Purwanti, Purwanti; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIt was descriptive research which aimed to find out the academic procrastination behavior of the students class VIII in Junior High School 13 Pontianak in academic year 2017/2018. The research problems were (1) What are the characteristics of academic procrastination? (2) What are the factors causing academic procrastination? (3) What are the effects of academic procrastination? (4) What are the efforts of counseling teacher to overcome the academic procrastination? This research aimed to describe and find out about (1) The characteristics of academic procrastination (2) The factors causing academic procrastination (3) The effects of academic procrastination (4) The efforts of counseling teacher to overcome the academic procrastination. The method used in this research was descriptive and survey research form. The population was the students of Junior High School 13 Pontianak class VIII in academic year 2017/2018 which was 36 students. This research used quantitative approach. The technique of data collection was indirect interview technique and it used questionnaire to collect the data. The result showed that academic procrastination behavior of the students class VIII in Junior High School 13 Pontianak was in high level. (1) The characteristics of academic procrastination was 74% with medium level, (2) The factors causing academic procrastination was 76% with high level, (3) The effects of academic procrastination was 80% with high level, (4) The effort of counselling teacher to overcome the academic procrastination was 84% with high level. It can be concluded that the academic procrastination of the students in class VIII of  junior high school 13 Pontianak can influence the students’ score and their future. Keywords: Academic Procrastination, Students’ Behavior, Effect